1998
DOI: 10.1002/(sici)1096-9063(199808)53:4<311::aid-ps775>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Fate of metsulfuron-methyl in soils in relation to pedo-climatic conditions

Abstract: The dependence of the behaviour of metsulfuron-methyl on soil pH was conÐrmed during incubations under controlled laboratory conditions with two French soils used for wheat cropping. The fate of [14C] residues from [triazine-14C]metsulfuron-methyl was studied by combining di †erent experimental conditions : soil pH (8É1 and 5É2), temperature (28 and 10¡C), soil moisture (90 and 50% of soil water holding capacity) and microbial activity (sterile and nonsterile conditions). Metsulfuron-methyl degradation was mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…Although metabolites were not identified in the present study, several metsulfuron‐methyl metabolites have been reported in previous studies. Pons and Barriuso (1998) found that hydroxyl‐metsulfuron‐methyl and amino‐triazine, referred to as methyl‐2‐(4‐hydroxy‐6‐methyl‐1,3,5‐triazine‐2‐yl carbamoylsulfamoyl) benzoate, and 4‐hydroxy‐6‐methoxy‐2‐amino‐1,3,5‐triazine, respectively, were the main intermediates from the two metabolic pathways involved in the degradation of metsulfuron‐methyl: O ‐demethylation and cleavage of sulfonylurea bridge of the methoxy‐triazine moiety. Sarmah et al (2000) noted that 2‐[( N ‐acetylcarbamoyl)carbamoylcarbamoylsulfamoyl] benzoic acid was the hydrolysis product with opened triazine ring for metsulfuron‐methyl.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although metabolites were not identified in the present study, several metsulfuron‐methyl metabolites have been reported in previous studies. Pons and Barriuso (1998) found that hydroxyl‐metsulfuron‐methyl and amino‐triazine, referred to as methyl‐2‐(4‐hydroxy‐6‐methyl‐1,3,5‐triazine‐2‐yl carbamoylsulfamoyl) benzoate, and 4‐hydroxy‐6‐methoxy‐2‐amino‐1,3,5‐triazine, respectively, were the main intermediates from the two metabolic pathways involved in the degradation of metsulfuron‐methyl: O ‐demethylation and cleavage of sulfonylurea bridge of the methoxy‐triazine moiety. Sarmah et al (2000) noted that 2‐[( N ‐acetylcarbamoyl)carbamoylcarbamoylsulfamoyl] benzoic acid was the hydrolysis product with opened triazine ring for metsulfuron‐methyl.…”
Section: Resultsmentioning
confidence: 99%
“…Sarmah et al (2000) noted that 2‐[( N ‐acetylcarbamoyl)carbamoylcarbamoylsulfamoyl] benzoic acid was the hydrolysis product with opened triazine ring for metsulfuron‐methyl. However, the complete degradation of triazine amine went slower than that of metsulfuron‐methyl in soil (Pons and Barriuso, 1998; Bossi et al, 1999), which may constitute an ever‐present and cumulative risk of metabolites to the environment and, eventually, to non‐target organisms. Despite this, the adverse effects caused by the metabolites of metsulfuron‐methyl along with the parent compound in soil have been presented (Boldt and Jacobsen, 1998; Li et al, 2005; Hollaway et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations